Relative humidity sensor employing optical fibers coated with ZnO nanostructures - Harith, Z.; Irawati, N.; Batumalay, Malathy*; Rafaie, H. A.; G., Yun II; Harun, S. W.; Nor, R. M.; Ahmad, H. (Indian Society for Education and Environment & Informatics Publishing Limited, 2015)
We demonstrate two simple relative humidity sensors using a tapered Plastic Optical Fiber (POF) and silica microfiber. The POF is tapered by chemical etching method whereby the fiber is immersed into acetone and polished by a sand paper to reduce the fiber’s waist diameter from 1 mm to about 0.4 - 0.5 mm. The silica microfibers were fabricated using flame brushing techniques. Both tapered fibers are then coated with zinc oxide (ZnO) nanostructures using sol-gel immersion on ZnO seeded and non-seeded fiber methods before it is used to sense relative humidity. It is found that the tapered POF coated with seeded ZnO performed better compared to tapered silica microfiber. The tapered POF coated with seeded ZnO based sensor has linearity and sensitivity of 94.41 % and 0.176 mV/%, respectively.